History Learning Resources Based on Local History: Kenduri Sko - Apdelmi (SINGOSARI, 2026)
Kenduri Sko is an intangible cultural heritage of the Kerinci community that embodies historical, social, religious, and educational values with significant potential as a source of history learning. However, the integration of local cultural heritage into history education remains limited, as classroom instruction continues to rely predominantly on textbooks and national historical narratives. This study aims to analyze the values embedded in the Kenduri Sko tradition and examine its potential as a history learning resource through the perspectives of ethnopedagogy and critical pedagogy. A qualitative approach employing an exploratory case study design was adopted. The research was conducted in Kerinci Regency, Jambi Province, Indonesia. Data were collected through participant observation, in-depth interviews with customary leaders and community members, and document analysis. The data were analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings reveal that Kenduri Sko functions not only as a ritual to honor ancestors and express gratitude for agricultural harvests but also as a medium for transmitting historical knowledge, collective memory, cultural identity, and local values, including mutual cooperation, social solidarity, deliberation, responsibility, and environmental stewardship. From an ethnopedagogical perspective, the tradition provides a contextual learning resource that connects students with their local historical and cultural experiences. Furthermore, from the perspective of critical pedagogy, Kenduri Sko encourages students to develop historical consciousness, critical thinking skills, and awareness of the dynamic transformation of cultural traditions in response to modernization and globalization. This study concludes that Kenduri Sko has substantial potential to be integrated into history education through project-based learning, field studies, and oral history approaches, thereby strengthening historical literacy, character education, and the sustainable preservation of local cultural heritage.